A comparison of the pictorial, print, and aural media on connotative meaning. final report - Anderson, James A.; Wisconsin State Univ., Oshkosh ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
This experiment sought to determine whether consistent dimensions of judgmental behavior concerning statements presented in a given medium would be identified with different measuring instruments, and whether the dimensions could be reliably reproduced in the different media. 768 subjects responded to 1 of 4 concepts presented through either the pictorial, written, or spoken medium on 50 semantic differential (s.d.) scales. Each of 35 S.d. Scales, which were loaded on 4 visual medium factors, was used to develop a comparison test of likert type (lt) scales. Then 4 groups, totaling 253 subjects, each evaluated 3 statements from a different medium and a different concept. To determine whether the sd results could be replicated without a paper and pencil test, a semantic space analyzer (ssa) was developed. It presented the sd scales on slides, and 87 subjects responded on a potentiometer. Analysis of variance and correlational analysis of mean scores on the 3 tests showed that the correlations were highly significant. Factor analysis of the sd, lt, and ssa scales yielded 2 major factors which appeared consistently with different media and different tests. Thus, the factors were indeed measuring similar judgmental behavior in the 3 media for messages equated in content and difficulty. (lh)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Auditory Stimuli; Electromechanical Aids; Factor Analysis; Filmstrips; Pictorial Stimuli; Rating Scales; Statistical Analysis; Verbal Stimuli